Study of maternal and foetal outcome in labouring women with severe and moderate anaemia - Srungavarapu, Revathi; Bidri, Shailaja R.; Yaliwal, Rajasri; Shiragur, Shobha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Anaemia, a significant public health concern in India. This study has evaluated the differences in maternal and foetal effects of moderate and severe maternal anaemia in Indian context. Methods: This prospective observational study was conducted among adult, term pregnant women with moderate and severe anaemia at the department of Obstetrics and Gynecology in a tertiary medical college between August and June 2024. A convenient sampling was used to recruit the patients after written informed consent. Detailed history, and clinical findings recorded, and descriptive statistical analyses were performed. Results: We recruited a total number of 245 pregnant women. The mean age was 25.3 years (SD 3.9 years). The prevalence of moderate anaemia was 63.3% (n=155) and severe anaemia was 36.7% (n=90). Severe anaemia had higher rates of packed cell and whole blood transfusions, and ICU admissions compared to moderate anaemia. Iron sucrose requirement was higher in the moderate anaemia group. Newborn had more frequent incidence of low-birth weight babies, and foetal distress in the severe anaemia group compared to the moderate anaemia group. No significant differences were found in foetal maturity, APGAR scores, meconium-stained liquor, or neonatal deaths between the moderate and severe anaemia groups. Conclusions: This study highlights the high prevalence of anaemia among pregnant women, with both moderate and severe cases posing significant risks. Effective management strategies like early screening and diagnosis, nutritional interventions, iron supplementation, medical management, education and awareness, and further research are required to reduce the prevalence and combat the condition.